Pendapatan Asli Daerah (PAD) Dengan Anggaran Pendapatan Dan Belanja Daerah (APBD) Di Kabupaten Jombang - Amanda Ardelia Putri; Sonny Fransisco Siboro; Elsa Safitri; Nabilla Aulia (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The aim of this research is to examine the relationship between the percentage of Original Regional Income (PAD) and the percentage of the Regional Revenue and Expenditure Budget (APBD) in Jombang Regency. The data analysis method used is a qualitative descriptive method that collects secondary data from official sources, such as local government financial reports. The research findings show that there has been a fluctuation in the ratio of PAD to APBD in Jombang Regency within the specified period. One of the implications of this research is the importance of increasing Original Regional Income as a source of original regional income for local governments in managing the APBD.